2018
DOI: 10.1109/jssc.2018.2837863
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Millimeter-Wave Single-Ended and Differential Fundamental Oscillators in CMOS

Abstract: This paper reports an approach to designing compact high efficiency millimeter-wave fundamental oscillators operating above the fmax/2 of the active device. The approach takes full consideration of the nonlinearity of the active device and the finite quality factor of the passive devices to provide an accurate and optimal oscillator design in terms of the output power and efficiency. The 213-GHz single-ended and differential fundamental oscillators in 65-nm CMOS technology are presented to demonstrate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 41 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The prototype chip implemented in a 65 nm CMOS process covers a 219-238 GHz frequency band with the output power of 3.4 dBm, while the minimum measured phase noise is −105.8 dBc Hz −1 at 10 MHz offset frequency. Furthermore, Wang et al reported an approach to design compact high-efficiency THz fundamental oscillators and it can be operated above half of the maximum frequency of the active device [63]. A 213 GHz signal-ended and differential fundamental oscillator was fabricated by 65 nm CMOS technology.…”
Section: Thz Oscillator (6g)mentioning
confidence: 99%
“…The prototype chip implemented in a 65 nm CMOS process covers a 219-238 GHz frequency band with the output power of 3.4 dBm, while the minimum measured phase noise is −105.8 dBc Hz −1 at 10 MHz offset frequency. Furthermore, Wang et al reported an approach to design compact high-efficiency THz fundamental oscillators and it can be operated above half of the maximum frequency of the active device [63]. A 213 GHz signal-ended and differential fundamental oscillator was fabricated by 65 nm CMOS technology.…”
Section: Thz Oscillator (6g)mentioning
confidence: 99%